Pengaruh Model Pembelajaran Two Stay Two Stray (TSTS) Terhadap Hasil Belajar Siswa Pada Materi PKN Kelas III SDN Kesamben 2 Ngoro Jombang - Kamelia, liza; Rahma Pratiwi, Emy Yunita; Dwinata, Anggara (IJPSE Indonesian Journal of Primary Science Education, 2024)
jbbb Currently there are still many teachers who use the lecture method, to use the two stray two stay learning model is still minimally used during learning. In this study, researchers wanted to find out whether the two stay two stray learning model had an effect on the learning outcomes of these students, this was the purpose of the study. This study used quantitative methods with a type of one-group pretest-postest design. The sample of this study was 16 students. Data collection methods are tests, questionnaires and documentation. The results of this study showed that before being given the action obtained an average value of 66.88 and after getting the action increased to 86.25. This study has a significant effect of 0.000. A significant value indicating 0.000 < 0.05 so that Hâ‚€ is rejected and Hâ‚ is accepted. This means that there is a positive influence and response from the use of the Two Stay Two Stray (TSTS) learning model on student learning outcomes in Class III PKN material at SDN Kesamben 2 Ngoro Jombang.